2017
DOI: 10.1007/s11356-017-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

Clusia hilariana and Eugenia uniflora as bioindicators of atmospheric pollutants emitted by an iron pelletizing factory in Brazil

Abstract: The objectives of this work were to evaluate if the pollution emitted by the pelletizing factory causes visual symptoms and/or anatomical changes in exposed Eugenia uniflora and Clusia hilariana, in active biomonitoring, at different distances from a pelletizing factory. We characterize the symptomatology, anatomical, and histochemistry alterations induced in the two species. There was no difference in the symptomatology in relation to the different distances of the emitting source. The foliar symptoms found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Observation of cells with evidence of cell death in the central vein of urban E. uniflora leaves suggests that there is a defense system formed by the accumulation of secondary metabolites that develop a protective barrier to prevent the progression of necrosis toward tissues healthy, as also observed by Sant'anna- Santos et al (2012) and Silva et al (2017). The urban site characteristics of the present study were enough to cause damage to E. uniflora leaves, similar to what was found for the influence of pollutants emitted by an iron pellet factory (Silva et al 2017). These findings provide more information for describing E. uniflora as a bioindicator species of the environment.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Observation of cells with evidence of cell death in the central vein of urban E. uniflora leaves suggests that there is a defense system formed by the accumulation of secondary metabolites that develop a protective barrier to prevent the progression of necrosis toward tissues healthy, as also observed by Sant'anna- Santos et al (2012) and Silva et al (2017). The urban site characteristics of the present study were enough to cause damage to E. uniflora leaves, similar to what was found for the influence of pollutants emitted by an iron pellet factory (Silva et al 2017). These findings provide more information for describing E. uniflora as a bioindicator species of the environment.…”
Section: Discussionmentioning
confidence: 82%
“…Visible damage to leaves, such as necrosis and chlorosis, as observed in E. uniflora leaves of the urban site, can be induced by particles carried by air, which is indicative of atmospheric pollution (Silva et al 2017). Silva et al (2017) observed that emissions from a pelletizing factory also caused visual damage to E. uniflora, including foliar abscission, necrosis and purplish coloration of young leaves. Silva et al (2015), previously also observed that E. uniflora individuals cultivated under the same conditions accumulated iron and sulfur in the leaves.…”
Section: Discussionmentioning
confidence: 98%
“…High Fe accumulation also occurs in the leaves in different plant tissue like spongy parenchyma cells and parenchyma cells of xylem on leaves of Avicennia schaueriana and Laguncularia racemosa, respectively (Arrivabene et al 2015) and in epidermal cells of leaves of C. hilariana (Silva et al 2017), suggests the storage of Fe in these tissues as the detoxification strategy in these species for the Fe excess. In P. urvillei, S. parviflora, S. viridis, and O. sativa, Fe accumulation was observed in different cellular compartments in the leaves.…”
Section: Fe Sequestration and Compartmentalizationmentioning
confidence: 99%
“…1B) (Neves et al 2009). Iron ore industries can disturb the nearby vegetation (Silva et al 2017;Silva et al 2020) which deserves attention because the exposition of sensitive species to Fe leads to a decrease in biodiversity over the years (Arrivabene et al 2015). The loss of the structure and function of cell membrane promoted by the lipid peroxidation due to the ROS excess promotes changes in the plant cells (Araújo et al 2020b), which can compromise the anatomy of organs and their functionality, thus impair key plant processes.…”
Section: Fe Impacts On Physiological Morphological and Metabolic Traitsmentioning
confidence: 99%
See 1 more Smart Citation